When The Police Are Trusted By The Public - Edi Saputra Hasibuan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Public confidence in the performance of the National Police is influenced by various factors, including direct public interaction when dealing with the police, the media, and information about the experiences of other parties when dealing with the police. So it is deemed necessary to identify the needs, desires and expectations of the community towards the performance of the National Police. It is intended that the implementation of police duties can be carried out professionally so as to optimize the performance of the National Police in order to protect, protect and serve the community; maintain public security and order; enforce the law. For this reason, continuous, integrated, systemic and systematic research is carried out to identify public confidence in the performance of the National Police so that the police can improve and maintain positive performance to realize Excellent Police Service